Methodology for commissioning : the three-phase approach - Killcross, Martin (Engineering cases, 2012)
Process plant commissioning in the chemical industry and related industries has an interesting dynamic, as there are few or no formal qualifications for commissioning a new plant. Process engineering has elements that address the subject, but the lack of published works on the topic has created the potential for commissioning to be a discipline that can be susceptible to serious problems during the key stage in a project's delivery. There is a three-step methodology that works well and has formed the basis of the author's career in process plant commissioning, which has now spanned more than 30 years.